2019
DOI: 10.1038/s41467-019-13503-9
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic coherence evolution in multidimensional ultrafast photochemical processes

Abstract: The complex choreography of electronic, vibrational, and vibronic couplings used by photoexcited molecules to transfer energy efficiently is remarkable, but an unambiguous description of the temporally evolving vibronic states governing these processes has proven experimentally elusive. We use multidimensional electronic-vibrational spectroscopy to identify specific time-dependent excited state vibronic couplings involving multiple electronic states, high-frequency vibrations, and low-frequency vibrations whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…In this work, we utilize recent advances in multidimensional spectroscopy, namely the advent of two-dimensional electronic-vibrational (2DEV) spectroscopy 30 , to study the origin and involvement of these highly mixed states-inaccessible to more conventional spectroscopies. A major advantage of this technique is the improved spectral resolution, afforded by infrared (IR) detection, which has successfully allowed for insight into ultrafast energy transfer, charge transfer, and proton transfer dynamics 6,19,[31][32][33][34] . IR detection also inherently makes this technique especially sensitive to the mixing of vibronic states because such mixing significantly alters vibrational transition moments.…”
mentioning
confidence: 99%
“…In this work, we utilize recent advances in multidimensional spectroscopy, namely the advent of two-dimensional electronic-vibrational (2DEV) spectroscopy 30 , to study the origin and involvement of these highly mixed states-inaccessible to more conventional spectroscopies. A major advantage of this technique is the improved spectral resolution, afforded by infrared (IR) detection, which has successfully allowed for insight into ultrafast energy transfer, charge transfer, and proton transfer dynamics 6,19,[31][32][33][34] . IR detection also inherently makes this technique especially sensitive to the mixing of vibronic states because such mixing significantly alters vibrational transition moments.…”
mentioning
confidence: 99%
“…Of course, 2DEV spectroscopy can function across a range of excitation and detection conditions dependent on the light sources employed and the compatibility of pulse shaping and detection capabilities. For example, Gaynor et al utilized a spectrally broadened UV pump source for the 2DEVS studies of the solar cell dye, [Ru-(dcbpy) 2 (NCS) 2 ] (dcbpy = 4,4 ′ -dicarboxy-2,2 ′ -bipyridine) (N3), 4,24 while Song et al demonstrated a 2DEV spectrometer with excitation frequencies ranging from 490 to 950 nm. 25 In a later paper by Gaynor et al, the applicability of a broadband mid-IR source was demonstrated; 26 however, the experimental implementation of broadband probes remains limited.…”
Section: Experimental Implementation Of 2devsmentioning
confidence: 99%
“…2 However, it soon became clear that oscillatory structures in 2DEV spectra of molecular complexes could reveal the role of vibronic interactions in facilitating energy flow. 3 A parallel investigation of vibronic effects in ultrafast charge transfer (CT) via 2DEVS was pioneered by Gaynor et al 4 A comparison of 2DEVS with the degenerate third-order 2D infrared [5][6][7][8] and 2D electronic [9][10][11] spectroscopies (2DIRS and 2DES,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major advantage of this technique is the improved spectral resolution, afforded by IR detection, which has successfully allowed for insight into ultrafast energy transfer, charge transfer, and proton transfer dynamics. 6,19,[31][32][33][34] IR detection also inherently makes this technique especially sensitive to the mixing of vibronic states because such mixing significantly alters vibrational transitions moments. Additionally, the further sensitivity provided by polarization-dependent 2DEV spectroscopy has been demonstrated in the spectral assignments of monomeric Chl a and b 35 , as well as in unveiling the role of vibronic coupling in a solar cell dye.…”
Section: Introductionmentioning
confidence: 99%